Innovation and Skills Workers of Mechanical Engineer to Design Smart Flush - Wan Omar Ali Saifuddin, Wan Ismail; Khalid, Jusoh (2018)
Smart Flush is an innovative product in mechanical engineering. All the skilled workers need to improve the quality of product that would be manufacture. The three objectives of this study are as follows: (i) to design automatic water level control based on electrical conductivity of the water; (ii) to improve the supply of water into the water tank as well as avoiding any accessing water; and (iii) to provide easy installation and maintenance. 5W + 1H concept are used to solve the problem. The existing water level for toilet flushing system employs mechanical method, which is commonly expose to mechanical failure. This research introduces the notion of water level controlling within the context of electrical conductivity of the water. System design integrates the electrical and electronic based water level sensing and couple with solenoids shut off valve in a wired environment. The system equipment is lower power consumption, equipment only work when the water level changes, usually is in a waiting state. Smart Flush approach would help in reducing water overflow and low water pressure in the piping system. Maintaining water level inside the toilet pump system is an essential aspect in order to avoid waste of water due to overflow.